2021
DOI: 10.1002/mabi.202100257
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐Adhesive Hydrogels Based on Dual Crosslinked Poly(2‐oxazoline)s

Abstract: The development of bone glues based on bone-adhesive hydrogels to allow for facile bone fracture fixation remains a major challenge. Herein, dual crosslinked hydrogels that combine tunable stiffness, ductility, and self-healing capacity are successfully synthesized. The resulting double network hydrogel is formed by chemical crosslinking of N-hydroxysuccinimide-functionalized poly(2-oxazoline)s(POx-NHS)"?> with amine-functionalized poly(2-oxazoline)s, and physical crosslinking of alendronate-functionalized pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…It was also demonstrated that this hydrogel exhibited an incredibly strong adhesion strength with a variety of surfaces including PTFE, glass, bone, and tooth enamel. For example, in the case of bovine bone, the highest adhesion strength was >10 MPa (Figure 3A), which was significantly higher than the values reported in the literature for other adhesives [ 1,2,4b,22 ] and for the commercial bone glue CA. This strong adhesiveness observed for the L‐DPZ hydrogel was therefore attributed to several mechanisms (Figure 1B): 1) Physical interactions, such as π – π stacking and hydrogen bonding interactions caused by the presence of abundant free catechol groups on L‐DOPA; [ 17a ] 2) Chemical interactions between the catechol–quinone groups and the amine or thiol groups by means of Michael addition and Schiff‐base reactions; [ 9,17a ] 3) Intramolecular crosslinking between the polymer chains and intermolecular associations between the polymer and ZIF‐8; [ 17a,20b,25 ] and 4) Coordination bonds between the phenolic moieties of L‐DOPA and the Zn 2+ ions originating from ZIF‐8.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…It was also demonstrated that this hydrogel exhibited an incredibly strong adhesion strength with a variety of surfaces including PTFE, glass, bone, and tooth enamel. For example, in the case of bovine bone, the highest adhesion strength was >10 MPa (Figure 3A), which was significantly higher than the values reported in the literature for other adhesives [ 1,2,4b,22 ] and for the commercial bone glue CA. This strong adhesiveness observed for the L‐DPZ hydrogel was therefore attributed to several mechanisms (Figure 1B): 1) Physical interactions, such as π – π stacking and hydrogen bonding interactions caused by the presence of abundant free catechol groups on L‐DOPA; [ 17a ] 2) Chemical interactions between the catechol–quinone groups and the amine or thiol groups by means of Michael addition and Schiff‐base reactions; [ 9,17a ] 3) Intramolecular crosslinking between the polymer chains and intermolecular associations between the polymer and ZIF‐8; [ 17a,20b,25 ] and 4) Coordination bonds between the phenolic moieties of L‐DOPA and the Zn 2+ ions originating from ZIF‐8.…”
Section: Resultsmentioning
confidence: 55%
“…Thus, based on the excellent lap shear strength of the L‐DPZ2 hydrogel, its adhesion strength was compared with those of other adhesives reported in the literature. As shown in Figure 3C,D, the average adhesion strengths of the L‐DPZ2 hydrogel with the glass (Figure 3C) [ 21 ] and bovine bone (Figure 3D) [ 1,2,4b,22 ] substrates were significantly higher than those of the reported adhesives and the commercially available bone glue cyanoacrylate (CA). Subsequently, the adhesiveness of the L‐DPZ2 hydrogel was further assessed by means of a tensile adhesion test, and as a result, the tensile strength was calculated to be 3.42 ± 0.13 MPa; this value is significantly higher than those of the PVA, L‐DP, and L‐DPZ1 systems, which were 1.30 ± 0.09, 1.70 ± 0.07, and 2.32 ± 0.17 MPa, respectively (Figure 3E).…”
Section: Resultsmentioning
confidence: 99%
“…The faster gelation time of PNIPAM- co -GMA-CYS was mainly due to the higher formation of sulfhydryl groups. The CYS conjugation in the PNIPAM polymer forms a sulfhydryl chemical cross-linkage with vertebral column glycoproteins …”
Section: Resultsmentioning
confidence: 99%
“…M. J et al [ 60 ] crosslinks N -hydroxysuccinimide-poly(2-oxazoline)s (Pox-NHS) and amine-poly(2-oxazoline)s/alendronate-poly(2-oxazoline)s (Pox-Ale) through Ca 2+ interact to form a hydrogel network. In addition, Ca 2+ can promote the repair of bone tissue to some extent.…”
Section: Application Of Self-healing Hydrogels In Tissue Engineeringmentioning
confidence: 99%